MODERN APPROACHES TO DIAGNOSTICS AND THERAPY OF VAGINAL INFECTIONS - Кравченко, Елена Николаевна; Куклина, Лариса Владимировна; Охлопков, Виталий Александрович; Набока, Маргарита Валерьевна (Mother and Baby in Kuzbass, 2017)
In modern obstetrical and gynecological practice, the problem of disturbing the vaginal microflora is one of the most urgent because of the possibility of developing a whole complex of complications affecting the reproductive function of women. Mixed variants of vaginal infections have been little studied, nevertheless, they must be distinguished, since different forms of coexistence of pathogens require an individual therapeutic approach.Objective – evaluation of the effectiveness of the use of a new combination gel form preparation for vaginal infections in pregnant women.Methods of research. The study included 200 pregnant women with vaginal infections: 100 women made up the basic group, received treatment with a new gel preparation Metrogyl Plus within 5 days. The comparison group consisted of 100 patients treated with Clion-D 100. The second stage involved lactobacilli providing colonization resistance of the vaginal biotope.Results. Efficacy after the end of treatment after 1 month was 99 % in the main group, 94 % in the comparison group (p = 0,12), relapses after treatment at 3 months were revealed in 2 % and 10 % of the observations, respectively, in the study groups (p = 0,02). Placental disorders, the threat of spontaneous abortion, polyhydramnios, gestational pyelonephritis, edema caused by pregnancy, and preeclampsia were collectively observed in the main group less frequently than in the comparison group (p = 0,025). Complications of childbirth and the postpartum period are also noted less frequently in the main group than in the comparison group, which is associated with a much smaller number of relapses after treatment (p = 0,004).Conclusion. Treatment of vaginal infections with a new gel form preparation in pregnant women is highly effective and is 99 %. The number of relapses after treatment with the combined preparation in the form of a gel is only 2 % after 3 months. Consequently, the use of an effective combination drug in the treatment of vaginal infections, reduces the incidence of complications of pregnancy, childbirth and the postpartum period.
Keywords: mixed vaginal infections; pregnancy; gel form of metronidazole; Florocenosis